Magnetic actuation and feedback cooling of a cavity optomechanical torque sensor - P. H. Kim (Nature Portfolio, 2017)
Although optomechanics enables precision metrology, measurements beyond mechanical properties often require hybrid devices. Here, Kim et al. demonstrate that a ferromagnetic needle integrated with a torsional resonator can determine the magnetic properties and amplify or cool the resonator motion.